PERANAN GURU FIKIH DALAM MENANAMKAN NILAI-NILAI FIKIH MUAMALAH PADA PESERTA DIDIK MTS NURUL IMAN POMALAA KABUPATEN KOLAKA - Ansar, Fachri; Nuryamin; Syamsuri; U., M. Shabir; Ruhaya, Besse (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The cultivation of fiqh muamalah values in schools is essential for developing students' Islamic character, particularly in social interactions and economic activities based on Islamic principles. However, the implementation of these values among students remains inconsistent, indicating the need for teachers to play a more active educational role. This study aimed to analyze the role of fiqh teachers in instilling fiqh muamalah values and to identify the values emphasized in learning activities at MTs Nurul Iman Pomalaa, Kolaka Regency. This research employed a qualitative approach with phenomenological and philosophical perspectives. Data were collected through observation, interviews, and documentation involving fiqh teachers, school leaders, and students. Data were analyzed through data reduction, data display, and conclusion drawing, while data validity was ensured through source, technique, and time triangulation. The findings revealed that fiqh teachers performed strategic roles as educators, mentors, motivators, role models, and evaluators in cultivating fiqh muamalah values. The values emphasized included honesty, trustworthiness, responsibility, mutual assistance, politeness, and fairness, which were implemented through classroom instruction, habituation, exemplary conduct, advice, and continuous supervision. The study highlights the importance of integrating fiqh muamalah values into daily educational practices to strengthen students' Islamic character.